KEPEMIMPINAN PENGHULU KAMPUNG DAYUN KECAMATAN DAYUN KABUPATEN SIAK TERHADAP PEMBANGUNAN DAN PEMBERDAYAAN MASYARAKAT TAHUN 2018-2019 - Anita "; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The leadership of the leader of the Dayun Village in community development and empowerment is very much needed in helping the community to be more independent and empowered. Dayun Village, Dayun District, Siak Regency is one of the successful villages and became the best village in Riau Province in 2018-2019. This study aims to describe the leadership of the Penghulu in the development and empowerment of the people of Kampung Dayun in 2018-2019. This study uses situational leadership theory to help answer objectives. This research uses a qualitative approach. The research location is in Dayun Village, Dayun District, Siak Regency. Then the data collection techniques used interview research and documentation. While the data analysis used qualitative descriptive data analysis techniques.             The results of the study indicate that the leadership of the Kampung Dayun leader manages power for the benefit of the community at large. Then in this study the leader of the Dayun Village used the Innovative-Progressive leadership type, this leadership model was not anti-society but emphasized common interests, transparent, real and accountable. Where all forms of development and empowerment programs starting from government and development are carried out to empower the village community. Furthermore, the leader of the Dayun Village carries out leadership in a normative manner according to the main duties and functions of the Penghulu so that they carry out development and community empowerment programs following the existing rules. In the leadership of the leader of Kampung Dayun embracing all parties, village officials and the community so that they succeeded in becoming the best and independent Village in Riau Province in 2018-2019. Keywords:  Headman Leadership, Community Development and Empowerment.